Auditoria administrativa para el mejoramiento de los servicios de la empresa Smartech, del cantón Quevedo, año 2014 - Macías Coello, Vanessa Paola (2016)
This research project deals with a management audit of the company "Smartech", located on the fourth No. 442 Tenth Street and Avenue Cortes Guzman June, the city of Quevedo, the objective of this subject of inquiry is to assess the administrative processes in order to improve the services provided by the company during the period 2014, the inductive methodology that allowed information through observation and analytical study of facts was applied, the deductive method where studies took place around was used the pre-established thematic analytical method was used to study the level of effectiveness of policies and internal control compliance by helping to identify risks and weaknesses in the administrative area. The results obtained were as follows: in relation to the first objective the company does not have adequate policies that allow the efficient fulfillment of its goals; in the study of the second objective internal control we are assessed using the COSO II, with an inherent risk of 40% under a risk control 29.24% under and audit risk of 2.34% relative to the third objective is analyzed administrative indicators which was obtained as a result of an effective compliance processes 93.75% directed to their activities and goals achieved, the ultimate objective of the audit results was determined by assessing the administrative processes and based on the findings it is recommended that the company should consider upgrading administrative policies, develop a training plan of internal control and audit their administrative area in order to meet the effective development of their operations.